Depression Of The Main Character Portrayed In Topdog/Underdog Play Script (2001) By Suzan Lori Parks - Farange Anjelia; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
This study aimed to discover and explained the depression of the main characters in Suzan Lori Parks play script entitled ‘’Topdog/Underdog’’ and this study was hoped to be utilized by further researcher. The data sources used in this study was the play script of ‘’Topdog/Underdog’’. In analyzing the data, the writer used descriptive qualitative research method through psychoanalysis approach. Data were obtained by using the techniques of reading, noting, and analyzing. While in classifying the data, the writer used Freud’s theory of psychoanalysis and analyzed the symptoms of the depressions used Bhowmik and Beck theory. After analyzing the data, the writer found that the drama script of suzan lori parks entitled ‘’Topdog/Underdog’’ contains 23 data of depressions were devided into 32 parts consists of 22 data of ID, 5 data of Ego and 5 data of Superego. While the data used 2 types of symptoms which emotional symptoms with 22 data and 1 cognitive symptom. From the data above it can be said that the most dominant data were Id and Cognitive symptoms.